If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5n + 15 = 3n Reorder the terms: 15 + 0.5n = 3n Solving 15 + 0.5n = 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 15 + 0.5n + -3n = 3n + -3n Combine like terms: 0.5n + -3n = -2.5n 15 + -2.5n = 3n + -3n Combine like terms: 3n + -3n = 0 15 + -2.5n = 0 Add '-15' to each side of the equation. 15 + -15 + -2.5n = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -2.5n = 0 + -15 -2.5n = 0 + -15 Combine like terms: 0 + -15 = -15 -2.5n = -15 Divide each side by '-2.5'. n = 6 Simplifying n = 6
| (X+5)(x+5)-49=0 | | -12=w+18 | | 5z-18-z+2= | | 10=(2*6)-8 | | 2x-3x-10=-9 | | B-2b=b+4b+2 | | 3(y-4)= | | 4x+8/4-2=x | | 2x^2-4x/x-2 | | 8+7x+4x=63 | | x+6=x.4 | | 99x+65=-4x | | z(4x^10y^11z^8)= | | 7+3C=-7 | | .25n=2n-21 | | 5(2x-12)+21=2x+21 | | w=4x(y-5) | | 210(-3)= | | 2(3+x)=20+3x | | 9y+2=11y+8 | | z(16xy^3z^3)= | | e^4y-ln(y^2+3)=2x | | Yy-2=y+1y-5 | | 27x^2-54x+2805=0 | | x+8=-2-2+5x | | 2w-4=2 | | 2w-4= | | k=11+9-8+99 | | -6x+8=6x+8 | | 17+b= | | log(5*3)= | | G(f(3))+g(g(8))= |